Closed spinal dysraphism: Think about it in the case of enuresis in children - Eric Michel Charlemagne Junior Kessi; Kaoutar Maslouhi; Ibrahima Dokal Diallo; Gray Delors Tsioukaka; Lina Belkouchi; Siham El Haddad; Latifa Chat; Nazik Allali (Radiology Case Reports)
Closed dysraphism is a rare but complex neurological disorder that can manifest as neurological deterioration secondary to an inherently tethered spinal cord. Spina bifida occulta is a spectrum of abnormalities ranging from lack of fusion of the vertebral arch without other associated abnormalities sometimes. An uro-neurological assessment is essential as this malformation may present urinary symptoms as the only urinary symptoms without other obvious neurological abnormalities. Spinal cord MRI is useful for diagnosing and determining the morphology of the pathology in young children with this condition.This case highlights a correlation between closed spinal dysraphism and enuresis in children.